2000
DOI: 10.1007/s002449910062
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of Heavy Metals (Hg, Ag, Pb, and Cu) in Gills and Digestive Gland of Mussels, Mytilus galloprovincialis (L.)

Abstract: The intracellular localization of heavy metals using autometallography (AUM) was studied in the gills and the digestive gland of the common mussel Mytilus galloprovincialis, after an experimental exposure to 0.1 mg L(-1) of Hg, 0.1 mg L(-1) of Ag, 0.1 mg L(-1) of Pb, and 0.1 mg L(-1) of Cu for 98 days. In the gills, autometallographical black silver deposits (BSDs) were localized in the dense bodies observed in the apical and in the basal part of the cells. Among metals, Hg presented the highest accumulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 2 publications
4
29
0
8
Order By: Relevance
“…This suggests that changes to the morphology and functioning of these cellular organelles, that are used as biomarkers of environmental stress in adult bivalves (i.e. lysosome abundance, alterations to membrane stability, lipofuscin accumulation (Etxeberria et al, 1995, Domouhtsidou and Dimitriadis, 2000, Moore et al, 2007, Rocha et al, 2016) could have similar utility in larvae for evaluating the cytotoxicity of internalized NPs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that changes to the morphology and functioning of these cellular organelles, that are used as biomarkers of environmental stress in adult bivalves (i.e. lysosome abundance, alterations to membrane stability, lipofuscin accumulation (Etxeberria et al, 1995, Domouhtsidou and Dimitriadis, 2000, Moore et al, 2007, Rocha et al, 2016) could have similar utility in larvae for evaluating the cytotoxicity of internalized NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of previous studies have addressed the life history and ecological features of the members of the genus Lithophaga (Valli et al, 1986;Scott, 1988;Brickner et al, 1993;Sinis, 1994-1995;ElMenif et al, 2007;Devescovi, 2009), including limited descriptions of the general anatomy of the genus (Turner and Boss, 1962;Simone and Goncalves, 2006), very little has been published on its ctenidial structure (Turner and Boss, 1962). Well-documented observations are available on other genera of Mytilidae: Mytilus, Mytella, and Perna (Aiello and Sleigh, 1972;Domouhtsidou and Dimitriadis, 2000;Gregory and George, 2000;Gregory et al, 2002;David and Fontanetti, 2005;David et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical examination of tissues after exposure showed localization of Hg in the gill of the green crab Carcinus maenas and suggested that it was bound to the cuticle/membrane complex whereas MMHg was distributed evenly in the cell/cytoplasm . Domouhtsidou and Dimitriadis (2000) found, in mussels, that Hg was concentrated in the abfrontal part of the gill filament and in the lysosomes and residual bodies of the gut tissue. Similarly, Jensen and Baatrup (1988) found that while Hg was widely distributed, it was concentrated in the apical part of intestinal epithelial cells and was mostly within cell lysosomes that are probably responsible for the sequestration and elimination of the metal.…”
mentioning
confidence: 95%